Objective assessment of intraocular flare after cataract surgery with combined primary posterior capsulorhexis and posterior optic buttonholing in adults. Issue 11 (15th May 2007) - Stifter, E; Menapace, R; Luksch, A; Neumayer, T; Vock, L; Sacu, S
Abstract : Aim: Combining primary posterior capsulorhexis (PPC) and posterior optic buttonholing (POBH) in cataract surgery is an innovative approach to prevent after-cataract formation effectively and to increase postoperative stability of the intraocular lens (IOL). The present study was designed to compare the postoperative intraocular flare after cataract surgery with combined PPC and POBH to conventional in-the-bag implantation of the IOL. Methods: Fifty consecutive age-related cataract patients with cataract surgery under topical anaesthesia in both eyes were enrolled prospectively into a prospective, randomised clinical trial. In randomised order, cataract surgery with combined PPC and POBH was performed in one eye; in the other eye cataract surgery was performed conventionally with in-the-bag IOL implantation keeping the posterior lens capsule intact. Intraocular flare was measured 1, 2, 4, 6, 12 and 24 h postoperatively, as well as 1 week and 1 month postoperatively, using a KOWA FC-1000 laser flare cell meter. Results: The peak of intraocular flare was observed in POBH eyes and eyes with in-the-bag IOL implantation 1 h postoperatively. In both groups, the response was steadily decreasing thereafter. During measurements at day 1, small though statistically significant higher flare measurements were observed in eyes with in-the-bag IOL implantation (p<0.05). At 1 week and 1 month postoperatively, intraocular flare measurements were comparable again (p>0.05). Conclusion: Cataract surgery with combined PPC/POBH showed slightly lower postoperative anterior chamber reaction compared to conventional in-the-bag implantation during 4-week follow-up, indicating that POBH might trigger somewhat less inflammatory response. This could be explained by the posterior capsule sandwiching between the optic and the anterior capsule, preventing direct contact-mediated myofibroblastic trans-differentiation of anterior lens epithelial cells with consecutive cytokine depletion.